Boycott In The Perspective Of The Quran: Interpretation Of Rejecting Actions That Reflect Justice And Unity Of The Ummah - Zayyadi, Ach; Ubaidillah, Ubaidillah (AL-WIJDÃN Journal of Islamic Education Studies, 2024)
A boycott is a deliberate collective action to stop supporting a particular entity as a form of peaceful protest. In the Islamic context, the concepts of justice and unity of the people are key principles taught in the Quran. This study aims to examine the concept of boycott from the perspective of the Quran, as well as analyze how this action can be used as a tool to uphold justice and strengthen the unity of Muslims. The research method used is a qualitative approach with text analysis from Quranic commentaries as well as historical and contemporary case studies. The study found that Quranic verses provide clear guidance on the importance of justice and solidarity among the Ummah, which can serve as an ethical basis for the act of boycott. Boycotts in the Quranic perspective can be seen as a form of upholding distributive and retributive justice, as well as a tool to strengthen Muslim solidarity. Historical and contemporary case studies show that boycotts can be an effective tool to garner support and demonstrate the solidarity and unity of the Ummah.  The results show that boycotts can have a significant impact in fighting for social justice and human rights, as well as in building unity and solidarity among Muslims. This research implies that boycotts when done appropriately and based on Islamic principles, can be a powerful tool to uphold social justice and strengthen the unity of the Ummah. The research also provides practical guidance for Muslim communities in designing and implementing effective boycotts by Islamic principles.   Keywords: Boycott, Social Justice, Quran, Unity of the Ummah